Incidence of steroid-induced diabetes mellitus among in-patients treated for COVID-19 infection in tertiary care centre - R. M., Suresh; T. M., Abhishek; P., Girish; V., Anjali; K., Venugopal (International Journal of Research in Medical Sciences, 2023)
Background: Glucocorticoids are one of the most effective lifesaving treatments for severe COVID-19 infection. The aim of this study was to review the incidence of glucocorticoid-induced diabetes and its associated risk factors in COVID-19 patients. Methods: This was a retrospective cohort study, Hassan institute of medical sciences, Hassan, Karnataka, from 1st July 2020 to 31st December 2021. Data were collected from the medical record department of all RTPCR/RAT-positive cases of COVID-19 patients admitted and treated for COVID-19, with a sample size of 521 patients. Results: In the present study of 521 patients with COVID-19 who received glucocorticoid therapy, 72 (13.8%) of the patients experienced GI-DM. In our series of 521 patients treated with steroid for respiratory diseases, old age and chronic smoking was an independent risk factor for GI-DM. Glucose tolerance declines progressively with age, resulting in a high incidence of type 2 diabetes and impaired glucose tolerance in the old population. Conclusions: In conclusion, this study found that 13.8% of in-patients treated for COVID-19 infection in a tertiary care centre developed GI-DM. The incidence of GI-DM was higher among patients who were older, had a history of smoking, and had hyperlipidaemia or malignancy. The study highlights the importance of monitoring blood glucose levels in patients receiving steroids for the treatment of COVID-19. Additionally, the results suggest that patients with certain risk factors may benefit from closer monitoring of blood glucose levels.